2017
DOI: 10.3390/pharmacy5040063
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Audit as a Useful Tool in the Process of Introducing Falsified Medicines Directive (FMD) into Hospital Pharmacy Settings—A Pilot Study

Abstract: Background: Recently, the European Union has introduced the Falsified Medicines Directive (FMD). Additionally, in early 2016, a Delegated Act (DA) related to the FMD was published. The main objective of this study was to evaluate the usefulness of external audits in the context of implementing new regulations provided by the FMD in the secondary care environment. Methods: The external, in-person workflow audits were performed by an authentication company in three Polish hospital pharmacies. Each audit consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The study was based on real-life dispensing scenarios identified in hospital pharmacies before the implementation of FMD. Methods (questionnaire and direct assessment) and the results of some of these assessments were published previously (12)(13)(14). All possible workflows were mapped and the implementation of the FMD requirements was studied to offer the best utilization of benefits of the FMD compliance.…”
Section: Methodsmentioning
confidence: 99%
“…The study was based on real-life dispensing scenarios identified in hospital pharmacies before the implementation of FMD. Methods (questionnaire and direct assessment) and the results of some of these assessments were published previously (12)(13)(14). All possible workflows were mapped and the implementation of the FMD requirements was studied to offer the best utilization of benefits of the FMD compliance.…”
Section: Methodsmentioning
confidence: 99%
“…The hospital pharmacy supplies all regional hospitals in the Austrian Tirol, 16 hospitals, so it works as a centralized hub for the region. The hospitals that are supplied do not have a hospital pharmacy [ 19 ].…”
Section: The Pharmaceutical Supply Chain: a Hospital Perspectivementioning
confidence: 99%
“…It dispenses a total of 2.25 million packages a year of the 112,000 orders received. The group of hospitals has a capacity of 4898 beds; in terms of logistics, the implication of the FMD for this type of operation is significant [ 19 ]. The FMD is a good opportunity to look at the supply chain and adapt it to a new reality and possibly optimize it.…”
Section: The Pharmaceutical Supply Chain: a Hospital Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Existing literature supports the need for pharmacy settings to establish and operationalize effective inventory controls. Religioni et al evaluated the usefulness of effective inventory controls when they investigated several Polish hospital pharmacies [ 18 ]. Audits included direct supervision, secondary data analysis, and an independently designed questionnaire.…”
Section: Literature Review Summarymentioning
confidence: 99%